The experience of sexual harassment victims in accessing counseling services at higher education institutions in Samarinda - Irawan, Andi Wahyu; Hidayati, Diajeng Laily; Dwisona, Dwisona (Universitas Islam Negeri Ar-Raniry, 2024)
This study aims to understand the experiences of sexual harassment victims in accessing counseling services at higher education institutions in Samarinda. The research addresses a gap in the literature, as most previous studies have focused more on the legal, sociological, and psychological aspects of sexual harassment but have not deeply explored the experiences of victims in accessing counseling services at the university level. This qualitative phenomenological research employed the Interpretative Phenomenological Analysis (IPA) approach. The participants consisted of four sexual harassment victims from two universities, one public and one religious-based institution. The findings of this study identified three main barriers. First, a lack of information regarding the counseling services available on campus led to delays in seeking help by the victims. Second, feelings of shame prevented victims from accessing counseling services as they were reluctant to share their traumatic experiences. This sense of shame was often exacerbated by fear of being blamed or perceived as overreacting by others, causing victims to keep their experiences to themselves. Third, the fear of social and academic stigma, including concerns about negative judgment from peers and lecturers, particularly if the perpetrator was a faculty member, became a significant obstacle for victims seeking help. Some victims even expressed concerns about the impact on their academic achievements if the incident became public. The study emphasizes the importance of policies that ensure easy access and clear information about counseling services, as well as efforts to reduce stigma, to encourage victims to seek help.